Rapid and Simple Approaches for Diagnosis of Staphylococcus aureus in Bloodstream Infections - Duan Rui; Wang Pei (Polish Journal of Microbiology, 2022)
Staphylococcus aureus is an important causative pathogen of bloodstream infections. An amplification assay such as real-time PCR is a sensitive, specific technique to detect S. aureus. However, it needs well-trained personnel, and costs are high. A literature review focusing on rapid and simple methods for diagnosing S. aureus was performed. The following methods were included: (a) Hybrisep in situ hybridization test, (b) T2Dx system, (c) BinaxNow Staphylococcus aureus and PBP2a, (d) Gram staining, (e) PNA FISH and QuickFISH, (f) Accelerate PhenoTM system, (g) MALDI-TOF MS, (h) BioFire FilmArray, (i) Xpert MRSA/SA. These rapid and simple methods can rapidly identify S. aureus in positive blood cultures or direct blood samples. Furthermore, BioFire FilmArray and Xpert MRSA/SA identify methicillin-resistant S. aureus (MRSA), and the Accelerate PhenoTM system can also provide antimicrobial susceptibility testing (AST) results. The rapidity and simplicity of results generated by these methods have the potential to improve patient outcomes and aid in the prevention of the emergence and transmission of MRSA.